Investigation of deoxidation of high-silicon austenitic sulfuric acid-resistant stainless steel - Dou, Guanxiong; Guo, Hanjie; Guo, Jing; Li, Shaoying; Yan, Yan; Wang, Zihan (Frontiers in Materials, 2022)
The oxygen content in high-silicon austenitic sulfuric acid-resistant stainless steels is one of the most detrimental parameters to their corrosion resistance. Based on the ion-molecular coexistence theory (IMCT), a thermodynamic model of the slag-steel reaction of austenitic stainless steel containing 5.0 wt% Si with CaF2-CaO-Al2O3-MgO-SiO2 pentabasic slag was developed to investigate the deoxidation reaction and the oxygen control mechanism of the steel. The model was validated through experiments proposed in this study. The results of the slag-steel reaction indicated that the equilibrium oxygen content was determined by the greater of two factors: w[O]%, Si obtained from the [Si]-[O] equilibrium reaction controlled by the activity of SiO2 and w[O]%, Al obtained from the [Al]-[O] equilibrium reaction controlled by the activity of Al2O3. The system temperature and the basicity of slag are the most crucial among the multiple variables affecting the equilibrium oxygen content compared with Al2O3 and CaF2 in slag. However, achieving an ultra-low oxygen steel, both a basicity of slag greater than two and a low activity of Al2O3 in slag should be maintained. The total oxygen content in steel can reach a minimum value of 3.4 ppm when the slag composition encompasses w(CaF2)% = 29.38, w(CaO)% = 44.07, w(SiO2)% = 14.69, w(MgO)% = 9.89, w(Al2O3)% = 1.96. The high basicity of slag reduces the total oxygen content of stainless steel, whereas the influence of redox reactions between Si and Al results in a higher Al content in steel and the formation of more inclusions during solidification. Thus, the optimal Al2O3 content is less than 4% and the optimal basicity is 2.4 during the refining process.